Mortality in Patients with Proximal Femoral Fracture During the COVID-19 Pandemic: A U.K. Hospital’s Experience - Mamarelis, Georgios (JB JS Open Access, 2020)
BACKGROUND: Coronavirus disease 2019 (COVID-19) is a worldwide pandemic, with a case mortality ratio of approximately 6.4% at the time of writing (May 2020). Mortality increases in elderly patients with comorbidities. Patients with hip fracture have an average age of 80 years, with an estimated 2.8 comorbidities per patient. Evidence is lacking regarding the mortality rate of patients with hip fracture admitted during the COVID-19 pandemic. Our aim was to investigate the mortality rate among patients with a proximal femoral fracture who were admitted to our hospital during the COVID-19 pandemic. METHODS: We conducted a retrospective review of all patients with a proximal femoral fracture admitted to Southend University Hospital in the U.K. from March to April 2020 (during the COVID-19 pandemic). Data collected included demographics (patient age, body mass index, sex), comorbidities, and blood test values along with COVID-19 diagnosis (based on positive microbiological sample and clinical and radiographic findings) and operative characteristics (time to operation, length of stay, American Society of Anesthesiologists [ASA] classification, Nottingham Hip Fracture Score). The primary outcome was the 30-day mortality rate for patients with a hip fracture who were COVID-19 positive or negative. Kaplan-Meier survival analysis was conducted along with Mann-Whitney U tests and Fisher exact tests. RESULTS: Forty-one patients were included in the study, of whom 37 had an available SARS-CoV-2 (severe acute respiratory syndrome-coronavirus 2) swab test result. The overall 30-day mortality was 22%. Eleven patients tested positive for COVID-19. There was a significant difference in the mortality rate between those who tested positive and those who tested negative (54.5% versus 7.69%, respectively; Fisher exact test, p = 0.004) and between the operative patients who tested positive and the operative patients who tested negative (37.5% versus 4.34%, respectively; Fisher exact test, p = 0.043). CONCLUSIONS: Patients with a proximal femoral fracture may be at higher risk for mortality during the COVID-19 pandemic. We noted that patients with a proximal femoral fracture who tested positive for COVID-19 had a higher 30-day mortality rate compared with those who tested negative. Additional research is required to ascertain the benefits of a reduction in time to operation. LEVEL OF EVIDENCE: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.